The Concept of One Health for Allergic Diseases and Asthma - Agache, Ioana; Laculiceanu, Alexandru; Spanu, Daniela; Grigorescu, Dan (Allergy, asthma & immunology research, 2023)
The worldwide prevalence of allergic disease is rising as a result of complex gene-environment interactions that shape the immune system and host response. Climate change and loss of biodiversity are existential threats to humans, animals, plants, and ecosystems. While there is significant progress in the development of targeted therapeutic options to treat allergies and asthma, these approaches are inadequate to meet the challenges faced by climate change. The exposomic approach is needed with the recognition of the bidirectional effect between human beings and the environment. All stakeholders need to work together toward mitigating the effects of climate change and promoting a One Health concept in order to decrease the burden of asthma and allergy and to improve immune health. Healthcare professionals should strive to incorporate One Health counseling, environmental health precepts, and advocacy into their practice.